Dietary spirulina supplementation modifies rumen development, fermentation and bacteria composition in Hu sheep when consuming high-fat dietary - Wang, Zhibo; Liang, Yaxu; Lu, Jiawei; Wei, Zongyou; Bao, Yongjin; Yao, Xiaolei; Fan, Yixuan; Wang, Feng; Wang, Daxiang; Zhang, Yanli (Frontiers in Veterinary Science, 2023)
Introduction This study aims to investigate the long-term effects of spirulina supplementation in a high-fat diet (HFD) on rumen morphology, rumen fermentation, and the composition of rumen microbiota in lambs. Spirulina is a blue-green microalgae that has been shown to have high nutritional value for livestock. Methods Fifty-four lambs were randomly divided into three groups: a normal chow diet (NCD) group, a high-fat diet (HFD) group, and a high-fat diet supplemented with 3% spirulina (HFD+S) group. Rumen morphology, rumen fermentation, and rumen microbiota were analyzed at the end of the study. Results Spirulina supplementation improved the concentration of volatile fatty acids and rumen papilla length. Additionally, there was a tendency for an increase in rumen weight and an upregulation of the genes Claudin-1, Claudin-4, and Occludin in the HFD+S group. Pyrosequencing of the 16S ribosomal RNA gene also showed that spirulina supplementation significantly changed the rumen microbiota composition in the HFD group, with a decrease in richness and diversity. Specifically, the relative abundance of Prevotella 9 and Megasphaera was significantly increased in the HFD group compared to the NCD group, while spirulina supplementation reversed these changes. Discussion This study suggests that 3% spirulina supplementation can improve rumen development and fermentation, and effectively relieve rumen microbe disorders in lambs caused by a high-fat diet. However, further research is needed to confirm the findings and to examine the long-term effects of spirulina supplementation in different types of livestock and under different dietary conditions.